EXAMINING THE IMPACT OF SOCIAL SECURITY PROGRAMS ON MILITARY PERSONNEL AND VETERANS: A SCIENTOMETRIC AND SCOPING REVIEW (Social Security Management Journal, 2024)
This study examines the role of social security programs in ensuring the well-being and economic stability of military personnel and veterans through a scientometric and scoping review approach. Using data from Scopus and Web of Science (WoS), an in-depth scientometric analysis was conducted to track publication trends, identify active countries and institutions, and analyze keyword co-occurrences. The top ten keywords identified are Social Security, Veterans, Military, Social Welfare, Disability, Military Spending, PTSD, Employment, Mental Health, and Social Policy. Additionally, the scoping review synthesized the literature to identify gaps and areas for further investigation. The findings suggest that increased military expenditure often results in lower economic growth and reduced social welfare, particularly in middle- and low-income countries, due to the diversion of resources from essential public services to military budgets. Conversely, social security programs such as those provided by the Providence VA Medical Center, have a positive impact on veterans' well-being, illustrating the importance of comprehensive support systems in military settings. The review also emphasizes the influence of public attitudes towards military conflicts on government policies and the necessity for robust social security measures in the face of aging populations and socio-economic challenges. This study uniquely contributes to our understanding of social security programs in military settings by emphasizing the importance of notational analysis in examining the intricate relationships between social support, technological advancements, and mental health, highlighting the need for comprehensive, interdisciplinary approaches to enhance socio-economic security, mental well-being, and human capital development among military personnel.